The importance of Civil Defense and protection actions in minimizing disasters in edifications and risk areas (Research, Society and Development, 2022)
The lack of resources, the overvaluation of land, the lack of specialized labor and the uncontrolled densification of buildings in cities make the population carry out constructions in risk areas, without monitoring by properly qualified professionals, who do not use good construction techniques and adequate constructive materials causing disaster risk. It is up to the municipalities, with the support of the States, when necessary, to act in the minimization of disasters in buildings and risk areas, through effective actions of protection and civil defense. Hence the importance of civil defense technicians having specific knowledge of the legislation in force and the pathological manifestations presented by the edifications, in order to act properly in risky situations. In the present work, 2 (two) case studies of risk situations experienced by the author are presented, as well as a proposal for specific documentation for the civil defense action in response to disaster situations.